MSME Empowerment Strategy to Enhance Market Competitiveness through the KKNT MBKM Program (Strategi Pemberdayaan UMKM dalam Rangka Meningkatkan Daya Saing Pasar Melalui Program KKNT MBKM) - Putri, Rizky Pratama; Faishal, Muhammad; Hibaturrachman, Farid; Amelia, Putri; Putri, Mahdiani Adinda; Mayra, Tri Okti; Zaleyata, Nailus Zahrani; Paraswati, Diyah Ayu; Yudistira, U Rizky; Hikmah, Nur; Tsalats, Zulfikar Ahmad (Indonesia Berdaya, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is a crucial strategy for enhancing market competitiveness in Indonesia, particularly in the face of globalization, which requires adaptation and innovation. Through the Thematic Community Service Program (Kuliah Kerja Nyata-KKN) of the Merdeka Belajar Kampus Merdeka (MBKM) initiative of Ahmad Dahlan University, students play an active role in supporting MSMEs in Yogyakarta by providing training and mentoring. This study aims to identify the challenges faced by MSMEs and provide solutions through a technology and innovation-based approach. The results of this program show an increase in MSME actors' understanding of digital marketing and the importance of halal certification, which contributes to increasing the competitiveness of their products.Abstrak: Pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan strategi penting untuk meningkatkan daya saing pasar di Indonesia, terutama dalam menghadapi globalisasi yang menuntut adanya adaptasi dan inovasi. Melalui Kuliah Kerja Nyata (KKN) Tematik Merdeka Belajar Kampus Merdeka (MBKM) Universitas Ahmad Dahlan, mahasiswa berperan aktif dalam mendukung UMKM di Yogyakarta dengan memberikan pelatihan dan pendampingan. Penelitian ini bertujuan untuk mengidentifikasi tantangan yang dihadapi UMKM dan memberikan solusi melalui pendekatan berbasis teknologi dan inovasi. Hasil dari program ini menunjukkan adanya peningkatan pemahaman pelaku UMKM terhadap pemasaran digital dan pentingnya sertifikasi halal yang berkontribusi pada peningkatan daya saing produknya.